2017
DOI: 10.1590/0037-8682-0423-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of the circulating cathodic antigen rapid urine test in the diagnosis of Schistosomiasis mansoni infection and evaluation of morbidity in a low- endemic area in Brazil

Abstract: Overall, the POC-CCA urine assay proved to be a useful test for diagnosing S. mansoni in a low-endemic area in Brazil. Severe clinical forms of schistosomiasis can be present even in such low-endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
2
25
1
1
Order By: Relevance
“…Our work adds to a growing body of literature using LCA to assess the performance of CCA [ 20 , 30 35 ]. Our estimates of sensitivity for both CCA and Kato-Katz were on the lower end of those observed in these other studies, and our specificity estimates for CCA were relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…Our work adds to a growing body of literature using LCA to assess the performance of CCA [ 20 , 30 35 ]. Our estimates of sensitivity for both CCA and Kato-Katz were on the lower end of those observed in these other studies, and our specificity estimates for CCA were relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of POC-CCA® was 86.6% and 73.5%, and specificity was 84.6% and 93.5%, when compared to K-K (two slides) and the reference method, respectively. The study by Ferreira et al 48 demonstrated that the POC-CCA® sensitivity values were 64.3%, 61.1%, 58.3%, and 55.5%, and specificity values were 74.5%, 74.8%, 75%, and 75.6% when compared to those of one, two, four, and six K-K slides, respectively. The use of two K-K slides as a reference method overestimates the sensitivity of the POC-CCA® due to the low efficiency of K-K in detecting true positive individuals with low levels of infection.…”
Section: Performance Of Circulating Antigen-based Rdt Diagnosis In Lomentioning
confidence: 97%
“…Applying LCA enables straightforward assessment of the prevalence estimates from each test by comparing the distributions of estimated test and estimated infection prevalence. 48 , 93 The introduction of statistical LCA is encouraged, as it yields more accurate sensitivities and specificities of new tests than those obtained by comparisons to an imperfect gold standard. 93 …”
Section: Antibody Detection Is a Valuable Tool To Identify Egg-negatimentioning
confidence: 99%
See 2 more Smart Citations